PERLINDUNGAN HUKUM BAGI KONSUMEN PADA KASUS KEAMANAN PANGAN OLEH KEJAKSAAN - Galih Puji Mulyono (University of Merdeka Malang, 2017)
Food safety and safety worth consumption, intended to ensure the safety and security of consumers in the use of goods and services or produce products of business actors so that consumers can avoid physical and psychological losses. Unsafe food products that are circulated and consumed in the community are deliberately made by the perpetrators by ignoring the right of the people to consume food that is safe for their living needs and violate existing legal provisions. Law enforcement in protecting and providing food security to the community is required as a form of law not just existing and enforced to the community but can help realize the true happiness. Law enforcement, in this case, the role of the prosecutor as a public prosecutor is needed to protect consumers and the creation of legal certainty and justice. Legal regulations applicable in the case of consumer protection are not interpreted as partial by law enforcement, but comprehensively with the basis of the main purpose of legal protection for the community. The role of prosecutors in law enforcement should be more considering the adverse impact on long-term consumer health should be considered and accountable to business actors.